2006
DOI: 10.4314/njsr.v7i1.12285
|View full text |Cite
|
Sign up to set email alerts
|

A huge polypoid uterine myoma causing severe primary postpartum haemorrhage: A report of one case

Abstract: Complications from uterine myomas in pregnancy could occur antenally, intrapartum or in the puerperium. One of such was diagnosed in a 36-year old para 2+0 who had successful gestation to term delivery in co-existence with a huge fibroid polyp and had spontaneous vaginal delivery of a life baby. She however developed severe primary postpartum haemorrhage prompting emergency postpartum digital vaginal myomectomy which was very helpful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
1
0
1
Order By: Relevance
“…Adagi et al reported a case of huge polypoidal uterine myoma causing severe primary post-partum hemorrhage prompting emergency postpartum digital vaginal myomectomy following which bleeding was controlled. 4 Our case has similar presentation except that initially it looked like a case of retained placenta. In addition to clinical assessment, radiological diagnosis (USG) also revealed placental tissue.…”
Section: Discussionsupporting
confidence: 54%
“…Adagi et al reported a case of huge polypoidal uterine myoma causing severe primary post-partum hemorrhage prompting emergency postpartum digital vaginal myomectomy following which bleeding was controlled. 4 Our case has similar presentation except that initially it looked like a case of retained placenta. In addition to clinical assessment, radiological diagnosis (USG) also revealed placental tissue.…”
Section: Discussionsupporting
confidence: 54%
“…Postnatal complications of pedunculated uterine polyp include PPH, infection, necrosis, prolapse of the polyp and inversion of uterus if the polyp is large. A case of pedunculated submucosal fibroid of lower segment causing PPH is recently reported13 and two cases of infection and necrosis and prolapse were reported in older literature 14…”
Section: Discussionmentioning
confidence: 99%
“…1 Komplikasi fibroid uteri pada kehamilan dapat muncul pada antenatal, intrapartumatau masa puerperium. 4 Ukuran mioma dan lokasi mioma dapat menjadi penyebab dilakukannya kelahiran dengan cara operasi sesar. 5 Walaupun banyak kemajuan signifikan pada terapi mioma secara bedah dan non-bedah, penanganan mioma pada seksiosesaria (CS; cesareansection) masih menjadi suatu kontroversi 6 Miomektomi merupakan tindakan pembedahan yang biasanya tidak dilakukan saat operasi sesar.…”
Section: Latar Belakangunclassified